Frequency-Domain Characteristics Response to Passive Exercise in Patients With Coronary Artery Disease - Zhang, Xiaodong; Zhang, Yahui (Frontiers in Cardiovascular Medicine, 2021)
Purpose: Enhanced external counterpulsation, as a kind of passive exercise, is a novel noninvasive therapy used to improve the peripheral perfusion in patients with coronary artery disease (CAD). However, whether frequency-domain characteristics of peripheral hemodynamics may benefit from passive exercise needs to be verified. Methods: We recruited 21 CAD patients and 21 healthy controls into this study. Ultrasonic blood flow velocity spectrum in left and right carotid common artery (LC, RC), right brachial and femoral artery (RB, RF) was monitored using ultrasonic Doppler. Frequency-domain characteristics before, during and after passive exercise were extracted from ultrasonic spectrum images. The first and second peak amplitude/frequency (y1, y2, x1, x2) and Power Spectral Energy Ratio (PSER) in the 0-2.05Hz/0.87Hz (p5, p6) were calculated by fast Fourier transform and power spectrum density analysis. Results: For the amplitude and frequency characteristics of spectrum, y1 in the LC of CAD patients was significantly decreased during exercise (p=0.036), while y2 was significantly decreased immediately after passive exercise (p=0.038). Besides those, y1 only in the RC and RB of controls was significantly decreased during exercise. Immediately after exercise, y2 in the LC of control was significantly lower than at baseline (p=0.014). For the energy ratio characteristics of spectrum, there was an opposite response in the two groups that p6 was significantly reduced and elevated in the LC of controls and in the RB of CAD patients during exercise, respectively (both p<0.05). Conclusions: Passive exercise reduces amplitude and frequency characteristics of carotid arteries, while there was an opposite response of energy ratio characteristics in the left carotid and right brachial arteries to passive exercise between CAD patients and controls. Additionally, energy ratio characteristics of spectrum in brachial artery was markedly elevated in CAD patients during passive exercise. Moreover, passive exercise only reduces amplitude characteristics of left carotid artery in the control group.